Editorial Commitment to Trust and Integrity in Science: Implications for Pain and Anesthesiology Research - Palermo TM; Bouhassira D; Davis KD; Hemmings Jnr HC; Hurley RW; Katz J; Pandit J; Price T; Schatman ME; Schwarz SKW; Turk D; Van de Velde M; et al. (Journal of Pain Research)
Tonya M Palermo,1,2 Didier Bouhassira,3 Karen Deborah Davis,4,5 Hugh C Hemmings Jnr,6 Robert W Hurley,7 Joel Katz,8 Jaideep Pandit,9,10 Theodore Price,11 Michael E Schatman,12,13 Stephan K W Schwarz,14,15 Dennis Turk,1 Marc Van de Velde,16,17 Matthew Wiles,18,19 Tony Yaksh,20 David Yarnitsky21 1Department of Anesthesiology & Pain Medicine, University of Washington, Seattle, WA, USA; 2Center for Child Health, Behavior & Development, Seattle Children’s Research Institute, Seattle, WA, USA; 3Inserm U987, APHP, UVSQ, Paris-Saclay University, Ambroise Pare Hospital, Boulogne-Billancourt, France; 4Department of Surgery and Institute of Medical Science, University of Toronto, Toronto, ON, Canada; 5Krembil Brain Institute, University Health Network, Toronto, ON, Canada; 6Department of Anesthesiology, Weill Cornell Medicine, New York, NY, USA; 7Department of Anesthesiology, Translational Neuroscience (formerly Pharmacology), and Public Health Sciences, Pain Outcomes Lab, Wake Forest University School of Medicine, Winston-Salem, NC, USA; 8Department of Psychology, York University, Toronto, ON, Canada; 9Nuffield Department of Clinical Neuroscience, University of Oxford, Oxford, UK; 10Nuffield Department of Anaesthesia, Oxford University Hospitals NHS Foundation Trust, Oxford, UK; 11Department of Neuroscience and Center for Advanced Pain Studies, University of Texas at Dallas, Dallas, TX, USA; 12Department of Anesthesiology, Perioperative Care, and Pain Medicine, NYU Grossman School of Medicine, New York, New York, USA; 13Department of Population Health – Division of Medical Ethics, NYU Grossman School of Medicine, New York, New York, USA; 14Department of Anesthesiology, Pharmacology & Therapeutics, The University of British Columbia, Vancouver, BC, Canada; 15Department of Anesthesia, St. Paul’s Hospital/Providence Health Care, Vancouver, BC, Canada; 16Department of Cardiovascular Sciences, Catholic University Leuven, Leuven, Belgium; 17Department of Anesthesiology, University Hospitals Leuven, Leuven, Belgium; 18Department of Academic Anaesthesia, Sheffield Teaching Hospitals NHS Foundation Trust, Sheffield, UK; 19Centre for Applied Health and Social Care Research (Care), Sheffield Hallam University, Sheffield, UK; 20Department of Anesthesiology & Pharmacology, University of California, San Diego, CA, USA; 21Department of Neurology, Rambam Medical Center, and Laboratory of Clinical Neurophysiology, Technion Faculty of Medicine, Haifa, IsraelCorrespondence: Tonya M Palermo, Seattle Children’s Research Institute, P.O. Box 5371, M/S BC-3, Seattle, WA, 98145, USA, Email tonya.palermo@seattlechildrens.org